Adventure game on stories of prophets / Azman Aizat Abdul Ghani - Abdul Ghani, Azman Aizat (2010)
Nowadays there are many ways to make learning more interesting. One of the ways is through playing games. This is because games have multimedia elements such as text, animation, graphic and audio. Moreover, games offer interactivity which makes the learning process fun and exciting. The project used adventure game in the teaching process which helps in learning about the stories of prophets. In addition, the game also combines the story telling approach with voice overs to make the make the user understands more about the stories of prophets. The project is implemented in English. The project is a game based learning targeting the primary school students aged seven to ten. The delivery platform is online.